Microplastics contamination of sea surface water in Banda Aceh City and Aceh Besar District, Aceh Province, Indonesia - Suci Budi Faradilla; Lisna Yanti Siregar; Nasrul Arahman; Zainal Abidin Muchlisin (Depik, 2025)
Plastic debris is one of the serious problems in urban cities, including Banda Aceh city and Aceh Besar district, Indonesia. This waste is degraded into a small particle called microplastics. This waste has the potential to pollute the waters in the coastal area. The objective of the present study was to analyse the microplastic contamination of the sea surface waters of Banda Aceh City and Aceh Besar District. Sea surface water was sampled from three locations, namely Gampong Jawa (Station 1), Alue Naga (Station 2), and Krueng Raya (Station 3) during January to March 2024. The results showed that there were four forms of microplastics found in the sea surface water sample, namely fragments, fibers, films, and pellets with nine colours, namely black, brown, blue, clear, red, yellow, green, pink, and purple. The fragments and black are the dominant form and colour of microplastic in the sea surface water of Banda Aceh city. The highest number of microplastic particles was found in Alue Naga waters (21.04 particles/L) and the least in Gampong Jawa waters (16.6 particles/L). Therefore, it is concluded that the surface of the seawater studied in this study has been contaminated with microplastics.Keywords: Microplastics Sea surface water Plastic waste Banda Aceh City Aceh Besar District